Constructing manufacturing-environmental model in Bayesian belief networks for assembly design decision support through fuzzy cognitive maps. (9th February 2009) - Cheah, Wooi Ping; Kim, Kyoung-Yun; Yang, Hyung-Jeong; Kim, Man-Sun; , Jeong-Sik Kim
This paper deals with the introduction of the Bayesian belief network (BBN) for the representation and reasoning about manufacturing environmental knowledge which captures the interactions between manufacturing-environmental factors and assembly design decision (ADD) criteria. BBN is used because it has a sound mathematical foundation, expressive representation scheme, powerful reasoning capability, efficient evidence propagation mechanism and proven track record in industry-scale applications. Unfortunately, the construction of conditional probability tables (CPTs) is both tedious and unnatural. Hence, fuzzy cognitive map (FCM) is introduced for knowledge acquisition because it is simple and user friendly. We also propose a method for the conversion of FCM into BBN.